Effects of the low carbohydrate, high fat diet on glycemic control and body weight in patients with type 2 diabetes: experience from a community-based cohort - Ahmed, Shabina Roohi; Bellamkonda, Sridevi; Zilbermint, Mihail; Wang, Jiangxia; Kalyani, Rita Rastogi (BMJ open diabetes research & care, 2020)
ObjectiveThe optimal diet to improve glycemia in patients with type 2 diabetes remains unclear. Low carbohydrate, high fat (LCHF) diets can improve glycemic control, but have not been investigated in real-world settings.Research design and methodsWe investigated effects of the LCHF diet compared with usual care in a community-based cohort of patients with type 2 diabetes by performing a retrospective study of 49 patients who followed the LCHF diet for ≥3 months, and compared glycemic outcomes with age-matched and body mass index (BMI)-matched controls who received usual care (n=75). The primary outcome was change in A1C from baseline to the end of follow-up.ResultsCompared with the usual care group, the LCHF group showed a significantly greater reduction in A1C (−1.29% (95% CI −1.75 to −0.82; p<0.001)) and body weight (−12.8 kg (95% CI −14.7 to −10.8; p<0.001) at the end of follow-up after adjusting for age, sex, baseline A1C, BMI, baseline insulin dose. Of the patients initially taking insulin therapy in the LCHF group, 100% discontinued it or had a reduction in dose, compared with 23.1% in the usual care group (p<0.001). The LCHF group also had significantly greater reduction in fasting plasma glucose (−43.5 vs −8.5 mg/mL; p=0.03) compared with usual care.ConclusionsIn a community-based cohort of type 2 diabetes, the LCHF diet was associated with superior A1C reduction, greater weight loss and significantly more patients discontinuing or reducing antihyperglycemic therapies suggesting that the LCHF diet may be a metabolically favorable option in the dietary management of type 2 diabetes.